METHOD FOR CONDUCT HIGH-PRECISION GEODESIC MEASUREMENTS USING GNSS SYSTEMS: METHOD FOR CONDUCT HIGH-PRECISION GEODESIC MEASUREMENTS USING GNSS SYSTEMS - Yanchev, Kiril (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The subject of the research is the conduct of geodetic measurements and mathematical processing of the results of these measurements, together with mathematical models and data from measurements of geodynamic processes in order to eliminate the known influence of observed global and regional geodynamic processes on geodetic measurements and networks and to take into account the influence of local geodynamic processes on them.